Three-dimensional psychosocial and-cultural model to develop creativity in primary education - Uriarte Latorre, Yohana del Carmen (2018)
The research proposes a three-dimensional psychosocial and cultural model to develop creativity in primary educa-tion. The benefits of boosting creativity in children between six and twelve years old were the starting point. On the other hand it aims to re-address the training process that teachers carry out in different areas. It interacted from the empirical-analytical paradigm with the intention to demonstrate the problem diagnosed in children from the multiple intelligences approach, and to justify the proposal to teachers. The research method was the propositive approach. Due to the fact it had a three-dimensional psychosocial and cultural model it counted with four measured dimensions: cognitive and metacognitive, affective-motivational, instrumental- knowledge and specific skills and the development dimension, which includes sociocultural and historical integration. Creativity was not managed suitably at teaching level in Lambayeque, therefore it was placed within an average level (48,9±9,57). The use of the proposed model is then justified due to the fact that there is a gap between an 80 and 90% that must be complied during the learning pro-cess (teaching- learning) in the different subjects. Children show multiple intelligences, in some cases potentialities and sometimes needs that aid to strengthen their creativity. This is a transversal model, since it does not suggest spe-cific strategies for each subject. Each educator will have the possibility to adapt the curricular contents, promote a creative environment accomplishing the mediator - facilitator and researcher- role of creative processes.